PENGARUH KUMULATIF ASAP ROKOK DAN STRES TERHADAP PENINGKATAN KADAR HORMON KORTISOL MENCIT - Sumintarti S (Journal of Dentomaxillofacial Science, 2002)
The aim of this study was to know the cumulative effect ofcigarette smoke and stress to the Cortisol hormoneincreasing of mice. The Observe was done to 36 malemices BALB/C, that were separated into 4 groups whichconsist of 9 mices per group, that groups were controlgroup, cigarette smoke group, electric foot shock group andcombine of cigarette smoke and electicfoot shockstress group. After they were given repeating andincreasing dose stressor during seven days, Cortisolhormone of mices were measured. The result of this studyshowed that combine of cigarette smoke and electric footshock stress group had increasing of Cortisol hormone washigher as significant difference (p<0.05) than controlgroups, cigarette smoke groups and electric foot shockgroup. Conclusion showed the cumulative effect ofcigarette smoke stressor and electric foot shock stressmore increasing Cortisol hormone of mice.